2007
DOI: 10.1158/1078-0432.ccr-06-2258
|View full text |Cite
|
Sign up to set email alerts
|

Myeloma Cell-Osteoclast Interaction Enhances Angiogenesis Together with Bone Resorption: A Role for Vascular Endothelial Cell Growth Factor and Osteopontin

Abstract: Purpose: Similar to osteoclastogenesis, angiogenesis is enhanced in the bone marrow in myeloma in parallel with tumor progression.We showed previously that myeloma cells and osteoclasts are mutually stimulated to form a vicious cycle to lead to enhance both osteoclastogenesis and tumor growth. The present study was undertaken to clarify whether myeloma cell-osteoclast interaction enhances angiogenesis and whether there is any mutual stimulation between osteoclastogenesis and angiogenesis. Experimental Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
1
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 42 publications
0
108
1
5
Order By: Relevance
“…It inhibits bFGF-induced proliferation (11), adhesion, migration, and survival of human umbilical vascular endothelial cells (26); decreases bone tumor -associated angiogenesis in the murine 5T2 multiple myeloma model (27); inhibits revascularization of the ventral prostate gland in castrated rats treated with testosterone (12); modulates a v h 3 and a v h 5 integrins (28); inhibits matrix metalloproteinase-2 and matrix metalloproteinase-9 (29); and modulates in cancer patients serum levels of proangiogenic growth factors including VEGF and bFGF (30). In vivo, zoledronic acid antiangiogenic activity may be also mediated via inhibition of osteoclasts, which actually produce angiogenic factors (31).…”
Section: Resultsmentioning
confidence: 99%
“…It inhibits bFGF-induced proliferation (11), adhesion, migration, and survival of human umbilical vascular endothelial cells (26); decreases bone tumor -associated angiogenesis in the murine 5T2 multiple myeloma model (27); inhibits revascularization of the ventral prostate gland in castrated rats treated with testosterone (12); modulates a v h 3 and a v h 5 integrins (28); inhibits matrix metalloproteinase-2 and matrix metalloproteinase-9 (29); and modulates in cancer patients serum levels of proangiogenic growth factors including VEGF and bFGF (30). In vivo, zoledronic acid antiangiogenic activity may be also mediated via inhibition of osteoclasts, which actually produce angiogenic factors (31).…”
Section: Resultsmentioning
confidence: 99%
“…These effects were only partially blocked by an antibody to IL-6, but were completely abrogated by inhibition of cellular contact, demonstrating the critical role of direct contact between myeloma cells and osteoclasts (50). Interactions between myeloma cells and osteoclasts have also been shown to result in an increase in the secretion of proangiogenic factors, and an increase in vascular tubule formation, suggesting a link between myeloma cells, osteoclasts and angiogenesis (40).…”
Section: Cell-cell Interactionsmentioning
confidence: 99%
“…In addition, VEGF can substitute for M-CSF in the induction of in vitro osteoclast differentiation (39). A recent study has demonstrated that blockade of both VEGF and osteopontin almost completely abrogated angiogenesis and bone resorption enhanced by coculture of myeloma cells and osteoclasts (40), suggesting VEGF may support osteoclastic bone resorption in myeloma.…”
Section: Vegfmentioning
confidence: 99%
“…22 Among the up-regulated genes, SPP1 was reported to enhance MM cell survival, migration, angiogenesis, and bone destruction. [23][24][25][26] Melanoma 2 (AIM2) was recently shown to be 1 of the 70 high-risk signature genes in MM, 11 and transcription factor Dp-1 (TFDP1) was reported to facilitate cell-cycle progression. [27][28][29][30] High expression of RAS p21 protein activator 1 (RASA1) in myeloma cells from patients with RAR␣2 ϩ myeloma suggested that Ras-Raf-mitogen-activated protein kinase kinase (MEK)-extracellular signal-regulated kinase (ERK) signaling pathways may be the RAR␣2-mediated downstream signaling pathway.…”
Section: Identification Of Molecular Pathways Associated With Rar␣2 Ementioning
confidence: 99%